Pengaruh Pendekatan Scientific Terhadap Kemampuan Berpikir Kreaktif Peserta Didik Pada Pembelajaran Tematik (SD Negeri 104204) - Yuswida Yanti Harahap (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Yuswida Yanti Hrp (1191111023). The Influence of the Scientific Approach in Thematic Learning on the Creative Thinking of Class IV Students at SD Negeri 104204 Sambirejo Timur (Quasi Experimental Research at SD Negeri 104204 Sambirejo Timur). The scientific approach is a teacher's way of teaching in which students participate actively. They go through several activities such as observing, asking questions, gathering information, trying new things, thinking, comparing ideas, and communicating with each other. The aim of this research is to determine the influence of a scientific approach on the creative thinking of students in class IV elementary school in learning Theme 9 Sub-theme 1 for the 2023 academic year. This research was conducted at SD Negeri 104204 Sambi Rejo Timur, with a population of 25 students whose address is Jl. Sempurna, Sambi Rejo Timur, Percut Sei Tuan. The method used is quasi experimental design. learners. The sample in this research was all fourth grade students at SD Negeri 104204 Sambi Rejo Timur, academic year 2023-2024. The sampling technique used Simple Random Sampling. The data collection technique used in this research was the observation technique. Questions and data collection tests through observation. The analysis technique uses simple regression analysis. The results of the research show that there is an influence of the scientific approach on the creative thinking of students in class IV elementary school in learning Theme 9 Sub-theme 1 for the 2023 academic year. This can be seen from the results of the control class critical thinking ability test with a significance level of 0.05, with a t value of 0.05. 2.506 with a significance level of 0.020. The results of the experimental class critical thinking ability test with a significance level of 0.05 obtained a calculated t value of 2.214 with a significance level of 0.037. So it can be said that the hypothesis proposed in this research is accepted.